Des informations « pas très importantes » dans les médias d’information en ligne : la couverture de l’actualité européenne à Chypre - Dimitris Trimithiotis (Communiquer)
This article explores the factors that influence the online coverage of politics, such as European news. It seeks to examine the capacity of online media to enhance the comprehensive coverage of politics. The study draws on approaches that place media digitization in its societal context. This involves recognizing the subjectivity of the implementation of new information and communication technologies. This theoretical assumption is examined in the Cypriot context. The analysis approaches media production on two different levels: (a) the message level and (b) the production process level. The article argues that there is a managerial logic in the implementation of the digital technology. Media organisations do not use the potentialities of digital technology for the benefit of a comprehensive coverage. On the contrary, online news media exploit the potential of digital technology to reduce their investment in personnel and in time covering topics that are classified as unlucrative.